Seeking refuge in human rights : complementary protection in international refugee law - McAdam, J (2004)
This thesis examines complementary protection the protection afforded by States to persons who fall outside the legal definition of a refugee in article 1A(2) of the 1951 Refugee Convention, but who nonetheless have a need for international protection. Human rights law has extended States' international protection obligations beyond the Refugee Convention, preventing States from removing individuals who would be at risk of serious harm if returned to their countries of origin. While a number of States have traditionally respected these additional human rights obligations, they have been reluctant to grant beneficiaries a formal legal status analogous to that enjoyed by Convention refugees. By examining the human rights foundations of the Convention, the architecture of the Convention, regional examples of complementary protection, and principles of non-discrimination, the thesis argues that the Convention is a lex specialis for all persons in need of international protection a specialized blueprint of legal status, irrespective of the legal source of the protection obligation. Chapter 1 identifies pre-1951 examples of complementary protection, demonstrating how the content of the status afforded to extended categories of refugees was historically the same as that granted to 'legal' refugees. It traces unsuccessful attempts at the international and European levels to codify a system of complementary protection, prior to the EU's adoption of the Qualification Directive in 2004. The Qualification Directive, examined in Chapter 2, represents the first supranational codification of complementary protection, but is hampered by a hierarchical conceptualization of protection that grants a lesser status to beneficiaries of 'subsidiary protection' vis-à-vis Convention refugees. Chapters 3 to 5 examine the CAT, ECHR, ICCPR and CRC to identify provisions which may give rise to a claim for international protection, beyond article 3 CAT, article 3 ECHR and article 7 ICCPR. Finally, Chapter 6 illustrates why all persons protected by the principle of non-refoulement are entitled to the same legal status, demonstrating the function of the Convention as a lex specialis for all persons in need of international protection.